2021
DOI: 10.3389/fmicb.2021.631445
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Diversity and Biomedical Potential of Microbes Associated With the Neptune’s Cup Sponge, Cliona patera

Abstract: Marine sponges are known to host a complex microbial consortium that is essential to the health and resilience of these benthic invertebrates. These sponge-associated microbes are also an important source of therapeutic agents. The Neptune’s Cup sponge, Cliona patera, once believed to be extinct, was rediscovered off the southern coast of Singapore in 2011. The chance discovery of this sponge presented an opportunity to characterize the prokaryotic community of C. patera. Sponge tissue samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…The microbial structure composition of C. varians‐ associated prokaryotes described here was consistent with the published data by Sacristán‐Soriano et al (2020) of C. varians specimens 1.700 km far, from inshore and offshore specimens in coral reef colonies in the Florida Keys, Northern Caribbean Sea. Likewise, the results are sustained by other Cliona species, where Proteobacteria is the dominant phylum (Easson et al, 2020; Ho et al, 2021; Jeong et al, 2015; Mote et al, 2021; Ramsby et al, 2018), indicating that a fraction of the core microbiome is vertically transferred and maintained in this species independent of its geographical location, while also there are signatures and components linked and horizontally transferred between the environmental microbiome and the sponge. Although the class of Alphaproteobacteria was also dominant in C. varians microbiota as in C. orientalis , in C. varians , by contrast, Gammaproteobacteria was the following more abundant class (Ramsby et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…The microbial structure composition of C. varians‐ associated prokaryotes described here was consistent with the published data by Sacristán‐Soriano et al (2020) of C. varians specimens 1.700 km far, from inshore and offshore specimens in coral reef colonies in the Florida Keys, Northern Caribbean Sea. Likewise, the results are sustained by other Cliona species, where Proteobacteria is the dominant phylum (Easson et al, 2020; Ho et al, 2021; Jeong et al, 2015; Mote et al, 2021; Ramsby et al, 2018), indicating that a fraction of the core microbiome is vertically transferred and maintained in this species independent of its geographical location, while also there are signatures and components linked and horizontally transferred between the environmental microbiome and the sponge. Although the class of Alphaproteobacteria was also dominant in C. varians microbiota as in C. orientalis , in C. varians , by contrast, Gammaproteobacteria was the following more abundant class (Ramsby et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the availability of the spectral library of a compound is very important in accelerating such identification. Several studies on metabolomics in sponges and their associated microbes reported that the use of LC-MS and GC-MS resulted in complex chemical profiles, thus requiring a reliable spectral library to assist the identification process; several studies used molecular networking methods combined with a cluster analysis in the identification of compounds (Alkhalifah, 2021;Erngren et al, 2021;Fagundes et al, 2021;Ho et al, 2021;Yuliana et al, 2011). Therefore, it is highly recommended to apply metabolomics on sponges and their associated microbes whose active compounds are not known using chromatographic techniques combined with MS by conditioning the type of compounds to be separated and conducting chemical profiles to facilitate a multivariate data analysis.…”
Section: Analytical Methods For Metabolomicsmentioning
confidence: 99%
“…Molecular networking has been used by several recent studies to analyze the metabolomic application on sponges and their associated microbes. The chemical shift profile of the NMR spectroscopy allows it to be analyzed with this molecular networking technique, provided that the available database is sufficient (Fagundes et al, 2021;Ho et al, 2021;Kouchaksaraee et al, 2020;Li et al, 2020).…”
Section: Chemometric Methods For Metabolomicsmentioning
confidence: 99%
“…The endophytic bacteria of samples from different sexes included specific phyla and genera, and most of them were metabolism-related bacteria. For example, among the specific bacterial phyla in the female algal bodies, Entotheonellaeota has the ability to synthesize bioactive substances (Ho et al, 2021), Armatimonadota and Planctomycetota can decompose and utilize complex polysaccharides (Wang et al, 2015), Nitrospirota is associated with N metabolism (Daims et al, 2015), and Marinimicrobia_SAR406_clade is associated with the dark fixation of dissolved inorganic carbon (DIC) (Guerrero-Feijóo et al, 2018). The only specific phylum in the male algal bodies was Elusimicrobiota, which consists of nitrogen-fixing bacteria (Zheng et al, 2016;Méheust et al, 2020).…”
Section: The Differences In Endophytic Bacterial Communities Between ...mentioning
confidence: 99%